Konsep Pendidikan Humanistik Perspektif Ki Hajar Dewantara dan Paulo Freire dalam Kritik Pendidikan di Masa Pandemi Covid-19 - Irma Rosyidah; Mujib Ridlwan (Institut Agama Islam Al-Hikmah Tuban, 2022)
Humanistik education is basicall an educational response to the human side of humanity considering that humans are basically referred to as pedagogic creatures which can be interpreted as beings who can teach and be taught. The purpose of this study is to describe the concept of humanistic education from the perspektive of Ki Hajar Dewantara and Paulo Freire in criticizing education during the Covid-19 pandemic. This study uses a research technique (library research), using a description of the analysis with a quality approach. The method used by the author to obtain data abaout the social setting, thought and strategy of humanistic education of Ki Hajar Dewantara and Paulo Freire by using a historical approach. The results of the study show that Distance Education (PJJ) or online is an oppressed education, there are indications that refer to the criteria of oppression, namely the dehumanization of education and the concept of learning far from cooperative.